INTERSTITIAL LUNG DISEASE IN PATIENTS WITH RHEUMATOID ARTHRITIS – FACTS AND PERSPECTIVE - Vanina Bozhilova; Spas Radev; Stanislava Alimanska; Stoilka Mandadzhieva (Science & Research, 2022)

(untitled)
Rheumatoid arthritis is the most common form of systemic autoimmune disease. It predominantly affects joints and synovial tissues, but there are also significant interstitial changes. More often in recent years there are patient cases of rheumatoid arthritis complicated by interstitial lung disease. It is questionable whether this pathology is the result of natural disease progression or is rather the side-effect of used medication. For the latter, there is general concern for the long-term use of Methotrexate. However, research carried out in a number of international research centers shows inhomogeneous data. Another point of consideration is which biomarkers should be used to follow-up patients and which risk factors can determine the population at risk of developing interstitial lung disease. Answering these questions would help adjust the therapy and mitigate the risk of developing this complication. Recently, the use of anti-fibrotic drugs as part of the treatment plan is being discussed, along with the need to separately determine joint and lung status of the patient. Currently, there are no existing, approved protocols for treatment of rheumatoid arthritis complicated with interstitial lung disease.